2022
DOI: 10.21608/ejhm.2022.266036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Celiac Disease Among Patients with Refractory Iron Deficiency Anemia in North-Western Saudi Arabia

Abstract: Background: Celiac disease (CD) is an immune-mediated intestinal disease caused by a hypersensitivity to gluten in genetically susceptible people. The most frequent type of anemia in the world is iron-deficiency anemia (IDA), which is also thought to be the most typical extra intestinal symptom of celiac disease. Aim: This study aimed to determine the prevalence of CD in patients with unexplained refractory IDA by using anti-tissue transglutaminase (anti-tTG) antibodies or by endoscopic biopsy in North-Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…(p=0.001, p<0.001, and p<0.001, respectively). In the same context, Rasha et al [20] they found that Individuals with refractory iron deficiency anaemia were more likely to have CD.…”
Section: Discussionmentioning
confidence: 95%
“…(p=0.001, p<0.001, and p<0.001, respectively). In the same context, Rasha et al [20] they found that Individuals with refractory iron deficiency anaemia were more likely to have CD.…”
Section: Discussionmentioning
confidence: 95%